Association between socioeconomic status and chronic obstructive pulmonary disease in Jiangsu province, China: a population-based study. Issue 13 (5th July 2021) - Zhang, Dan-Dan; Liu, Jian-Nan; Ye, Qing; Chen, Zi; Wu, Ling; Peng, Xue-Qing; Lu, Gan; Zhou, Jin-Yi; Tao, Ran; Ding, Zhen; Xu, Fei; Zhou, Linfu
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a common public health problem worldwide. Recent studies have reported that socioeconomic status (SES) is related to the incidence of COPD. This study aimed to investigate the association between SES and COPD among adults in Jiangsu province, China, and to determine the possible direct and indirect effects of SES on the morbidity of COPD. Methods: A cross-sectional study was conducted among adults aged 40 years and above between May and December of 2015 in Jiangsu province, China. Participants were selected using a multistage sampling approach. COPD, the outcome variable, was diagnosed by physicians based on spirometry, respiratory symptoms, and risk factors. Education, occupation, and monthly family average income (FAI) were used to separately indicate SES as the explanatory variable. Mixed-effects logistic regression models were introduced to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for examining the SES-COPD relationship. A pathway analysis was conducted to further explore the pulmonary function impairment of patients with different SES. Results: The mean age of the 2421 participants was 56.63 ± 9.62 years. The prevalence of COPD was 11.8% (95% CI: 10.5%–13.1%) among the overall sample population. After adjustment for age, gender, residence, outdoor and indoor air pollution, body weight status, cigarette smoking, and potential study area-level clustering effects, educational attainment was negatively associated with COPD prevalence in men; white collars were at lower risk (OR: 0.60, 95% CI: 0.43–0.83) of experiencing COPD than blue collars; compared with those within the lower FAI subgroup, participants in the upper (OR: 0.68, 95% CI: 0.49–0.97) tertiles were less likely to experience COPD. Such negative associations between all these three SES indicators and COPD were significant among men only. Education, FAI, and occupation had direct or indirect effects on pulmonary function including post-bronchodilator forced expiratory volume in 1 s/forced vital capacity (FEV1 /FVC), FEV1, FVC, and FEV1 percentage of predicted. Education, FAI, and occupation had indirect effects on pulmonary function indices of all participants mainly through smoking status, indoor air pollution, and outdoor air pollution. We also found that occupation could affect post-bronchodilator FEV1 /FVC through body mass index. Conclusions: Education, occupation, and FAI had an adverse relationship with COPD prevalence in Jiangsu province, China. SES has both direct and indirect associations with pulmonary function impairment. SES is of great significance for COPD morbidity. It is important that population-based COPD prevention strategies should be tailored for people with different SES.